2015
DOI: 10.1523/jneurosci.4655-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

proBDNF and p75NTR Control Excitability and Persistent Firing of Cortical Pyramidal Neurons

Abstract: Persistent firing of entorhinal cortex (EC) pyramidal neurons is a key component of working and spatial memory. We report here that a pro-brain-derived neurotrophic factor (proBDNF)-dependent p75NTR signaling pathway plays a major role in excitability and persistent activity of pyramidal neurons in layer V of the EC. Using electrophysiological recordings, we show that proBDNF suppresses persistent firing in entorhinal slices from wild-type mice but not from p75NTR-null mice. Conversely, function-blocking proBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 41 publications
(3 reference statements)
3
40
0
Order By: Relevance
“…While BDNF has the ability to increase neuronal excitability and synaptic strength [5, 20, 71, 76, 78, 130, 171], proBDNF can reduce neuronal excitability, decrease synaptic efficiency, and facilitate synaptic depression [53, 98, 126, 162, 165, 167]. …”
Section: Family Of Bioactive Bdnf Ligandsmentioning
confidence: 99%
“…While BDNF has the ability to increase neuronal excitability and synaptic strength [5, 20, 71, 76, 78, 130, 171], proBDNF can reduce neuronal excitability, decrease synaptic efficiency, and facilitate synaptic depression [53, 98, 126, 162, 165, 167]. …”
Section: Family Of Bioactive Bdnf Ligandsmentioning
confidence: 99%
“…Increased complexity of the dendritic spines of CA1 hippocampal pyramidal neurons, changes to glutamatergic receptors, and increased cholinergic transferase activity in p75 exonIII−/− mice have also been demonstrated [124,131,133,134]. In addition, it has been reported that, in adult mice lacking p75 NTR , the excitability and persistent firing of pyramidal neurons in layer 5 of the entorhinal cortex is unregulated due to a lack of inhibition [135]. As the expression of p75 NTR in the entorhinal cortex occurs in the innervating cBF axons, the role of p75 NTR could be to regulate cBF neuron structure or function thereby indirectly mediating the inhibition or activation of post-synaptic pyramidal cell activity.…”
Section: Effects Of Loss Of P75 Ntr Expression On Behaviour and Synapmentioning
confidence: 95%
“…) and suppressed persistent firing (Gibon et al . ), respectively. These results suggest that proBDNF can also act as an endogenous ligand to directly regulate LTD and to control neuron excitability.…”
Section: Prodomains As Part Of Active Pro‐protein Precursorsmentioning
confidence: 95%
“…Likewise, the unprocessed neurotrophin 3 (proNT3) triggers apoptosis in inner ear neurons and sympathetic neurons which co-express p75NTR and sortilin (Yano et al 2009;Tauris et al 2011). Application of proBDNF to p75NTR-expressing hippocampal or entorhinal slices enhanced long-term depression (LTD) (Woo et al 2005) and suppressed persistent firing (Gibon et al 2015), respectively. These results suggest that proBDNF can also act as an endogenous ligand to directly regulate LTD and to control neuron excitability.…”
Section: Prodomains As Part Of Active Pro-protein Precursorsmentioning
confidence: 99%